Design and fabrication of a magnetic bearing using magnetic edge effect. (8th March 2021) - Hossain, Md Alamgir; Sufian, Md Abu; Rashid, Fazlur; Shahadat, Mhia Md Zaglul
Abstract: This paper presents the design, fabrication, and performance test of a magnetic bearing employing no active components. In this study, the magnetic bearing was fabricated using a magnetic edge effect. Four large and three small hollow Neodymium (Nd) magnets were used of the same thickness, same internal diameter but different outer diameters. Small magnets were rigidly attached in the rotor and large magnets were fixed in the casing. In magnetic edge effects, a rotor along with small magnets was suspended inside the casing. Using stroboscope, rpm of the rotors were measured at no load, 0.5 N, 1.0 N, 1.5 N conditions for a different number of magnetic bearings in series, and the corresponding torque was calculated. After that, all the data were compared to the ball bearing set up in the same rotor. This paper shows that the speed of the magnetic bearing was doubled than the ball bearing with the same loading conditions. Required torque was 1.5 times greater in the case of ball bearing when compared to the magnetic bearing. The developed system is capable of suspending a rotor at a stable steady-state position. This suspension is accomplished by the edge effect of Nd round hollow magnets.